The persistent effects of COVID-19 on the economy and fiscal capacity of Indonesia - Heru Iswahyudi (Jurnal Ekonomi dan Pembangunan, 2025)
Does the pandemic of COVID-19 have persistent or transitory effects on Indonesia’s economy and fiscal capacity? This article addresses the empirical answer to this question by conducting unit root tests on time series data of Gross Domestic Product (GDP), income tax revenue, Value-Added Tax (VAT) revenue, the ratio of income tax revenue to GDP, and the ratio of VAT revenue to GDP covering the period from 1984 to 2019. The results find the presence of unit root process in these time series which imply that the shock from the pandemic may persistently lower the path of economic output and fiscal capacity of Indonesia.